The Development and Evaluation of Netball-Specific High-Intensity Interval Training Sessions: The Netball-HIIT Study - Narelle Eather; Katelyn Stansfield; Mark Babic; David R. Lubans (MDPI AG, 2024)
This two-phase study involved the design, development, and evaluation of netball-specific high-intensity interval training sessions (Netball-HIIT) for use with netballers of varied ages and abilities. In Phase 1 (2020), a systematic analysis of netball GPS data from 30 netball players and gameplay video footage (10 h) was conducted, followed by the design and testing of five 8 min Netball-HIIT sessions involving 100 netball players (age 21 ± 8.44 years; Australia). In Phase 2 (2021), the feasibility and preliminary efficacy of delivering one Netball-HIIT session each week for five weeks was assessed using a two-armed, dose-matched, randomized, controlled feasibility study with netball players (born in 2010) (Netball HIIT n = 15; Netball Knee Program: NKP n = 15). Cardiorespiratory and muscular fitness was assessed at baseline and 6 weeks. Data were analyzed using linear mixed models and Cohen's d effect sizes. Netball-HIIT sessions were highly rated by players, and higher average (139 bpm) and peak heart rates (156 bpm) were detected amongst Netball-HIIT participants (KNP = 127 bpm and 152 bpm). We observed a large effect for cardiorespiratory fitness (+2.4 laps, d = 0.89), and a small to medium effect for muscular fitness (push-ups +1.2, d = 0.49; standing jump +0.8 cm, d = 0.36) in favor of Netball-HIIT, suggesting that coach-led Netball-HIIT may provide a time-efficient and effective training component for use in netball.